Functionalized graphene, method for producing functionalized graphene, and uses thereof

JP2025032244AInactive Publication Date: 2025-03-11EVONIK OPERATIONS GMBH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024213293
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-07-01
Filing Date
2024-12-06
Publication Date
2025-03-11
Estimated Expiration
Not applicable · inactive patent

Smart Images

  • Figure 2025032244000004
    Figure 2025032244000004
  • Figure 2025032244000005
    Figure 2025032244000005
  • Figure 2025032244000006
    Figure 2025032244000006
Patent Text Reader

Abstract

To provide a method for functionalizing a graphene material, the functionalized graphene material itself and uses thereof.SOLUTION: In a process for functionalizing a graphene material, the graphene material is reacted at least partially with at least one silane having the structure Y-Si(OR1)(OR2)(OR3), wherein Y is an alkyl, olefin or aromatic moiety, a combination of these moieties, or a functional organic group, selected from: carboxy, carbonyl, hydroperoxycarbonyl, halogenyl, sulfo, sulfino, sulfeno, cyano, formyl, oxo, thioxo, a combination of these groups, or a combination of alkyl, olefin or aromatic moiety and the functional organic group, and R1, R2, R3 are alkyl, olefin or aromatic moieties which are branched or unbranched and are pairwise identical or nonidentical, and the at least partial reaction is carried out during mixing of the silane(s) with the graphene material.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for the functionalization of graphene materials, to the functionalized graphene materials themselves and to uses thereof.

[0002] Graphene, its production, properties and applications are described in technical literature, e.g. Roempp online https: / / roempp.thieme.de / lexicon / RD-07-02758 A detailed paper is published in.

[0003] Each carbon atom in graphene is covalently bonded to three neighboring atoms by sigma bonds, just like in graphite. The CC bond length is 142 pm. The atoms are sp 2 hybridization, and the sigma bonds lie in one plane. Thus, graphite has a planar structure. Each atom has partially filled p z There are still orbitals remaining. These p z The orbitals are orthogonal to the plane of the bonds, forming a delocalized π-electron system that determines the electronic properties of graphene.

[0004] Crystallographically, graphene has a unit cell vector

number

[0005] In the present invention, a "graphene material" refers to a material conforming to ISO / TS 80004-13, i.e. - Graphene - Graphene-based carbon materials - Single-layer, double-layer and triple-layer graphene - Epitaxial graphene - Exfoliated graphene - Few-layer graphene - Multi-layer graphene - Few-layer nanoribbons - Graphene Nanoplates - Graphene Nanoplatelets - Graphene nanosheets - Graphene Microsheets - Graphene nanoflakes - Graphene nanoribbons - Graphene oxide - Graphene oxide nanosheets - Multi-layer graphene oxide - Graphene Quantum Dots - Graphite - Graphite Nanoplate - Graphite nanosheets - Graphite Nanoflakes - Graphite Oxide - Reduced graphene oxide Or a mixture thereof.

[0006] Graphene materials are used in many technological fields.

[0007] As an example, China Patent Publication No. 109504318 presents a method for using graphene oxide and aluminum oxide to modify polystyrene film for flexible printed circuits.

[0008] WO2018019905 discloses a method for coating a metal substrate with one or several monolayer graphene sheets using a binder substance.

[0009] WO2015055252 discloses vinyl silanes that can be used in rubber compounds containing graphene materials, for example in the manufacture of tires.

[0010] CN104342003 presents a water-based coating for glass doors that repels dust and bacteria, in which graphene is used inter alia to produce the coating.

[0011] CN105056879 teaches how a composition containing polyester fibers and graphene can improve the mechanical properties of asphalt.

[0012] A concentrate containing graphene and sulfonamide in addition to other materials can be used to prepare vulcanized rubber mixtures.CN Patent Publication No. 107459717 discloses such a concentrate and a method for its preparation.

[0013] Graphene materials are also used to prevent decay in construction materials: CN108947394 teaches that Portland cement is compounded with modified graphene oxide in addition to other materials.

[0014] WO2019145307 discloses compositions comprising polymeric inorganic nanoparticles and their use in lubricants and antifriction agents for metal surfaces. Graphene is used as the nanoparticles in particular.

[0015] Graphene materials are commercially available as powders and often have a very low bulk density, e.g. in the range of 2-400 g / l. In addition to the low bulk density, most graphene materials also have poor flowability or generate a high content of dust when poured. This leads to poor handling, problems during weighing and feeding, and should be considered as a risk from the standpoint of environmental protection and occupational safety.

[0016] This poor handling becomes evident when powders are incorporated into elastomer systems, for example during rubber compounding. Correct timing and duration of powder filler incorporation is important for the production of a good filled rubber compound. The filler is introduced into the compounding chamber by a hopper and then pushed towards the rotating rolls by a pneumatic plunger.

[0017] In the prior art, it is certainly known how to improve or enable the dispersion of graphene materials or other fillers in matrix systems using silanes or siloxanes, most often in substoichiometric amounts.

[0018] However, there is still a need for industrial methods to handle or avoid the large amounts of dust that are generated when using powdered graphene materials, firstly because it causes contamination and makes it difficult to measure the amount of filler that is actually introduced into the matrix system, and secondly because the dust must be vacuumed or disposed of for work safety and environmental protection reasons.

[0019] Furthermore, the dust and generally low bulk density of graphene materials increase the cost of introducing them into a desired matrix system. For example, similar challenges arise when producing thermoplastic compounds filled with graphene materials in an extruder. For these reasons, it may be impossible or difficult to reliably supply powdered graphene materials in a timely manner in the manufacturing process of a thermoplastic resin system.

[0020] It was therefore an object of the present invention to process graphene materials into products which have improved flowability and / or increased bulk density, generate less dust during processing and can therefore be better incorporated into commercially important matrix systems.

[0021] Surprisingly, it has been found that this problem is solved by silane-functionalized graphene materials.

[0022] The subject of the present invention is a method for the functionalization of a graphene material, comprising at least partially reacting the graphene material with at least one silane, the at least one silane having the structure Y-Si(OR 1 )(OR 2 )(OR 3 Y is a branched or unbranched alkyl, olefinic or aromatic group, a combination of said groups, or an organic functional group selected from carboxy, carbonyl, hydroperoxycarbonyl, halogenyl, sulfo, sulfino, sulfeno, cyano, formyl, oxo, thioxo, hydroxy, amino, imino, hydrazino, epoxy, sulfanyl, fluoro, a combination of said groups, or a combination of an alkyl, olefinic or aromatic group with said organic functional group; R 1 , R 2 , R 3 are branched or unbranched, pairwise identical or non-identical alkyl, olefinic or aromatic groups, and at least a partial reaction takes place during mixing of the silane with the graphene material.

[0023] After carrying out the method of the present invention, the graphene material is obtained in the form of granules.

[0024] In the present invention, the granules are https: / / roempp.thieme.de / 35IDR Based on the definition of the granules, the term refers to a collection of asymmetric agglomerates made up of powder particles. The agglomerates have an uneven surface and do not have a uniform geometric shape. The determination of the bulk density according to DIN ISO 697:1984-01 and the measurement of the angle of repose according to DIN ISO 4324:1983-12 can be used to characterize the granules.

[0025] The method according to the invention has the advantage that it is very easy to carry out and thus results in graphene materials with less dust and clearly better flowability compared to conventional graphene materials, thus realizing added value in dispersion into various matrix systems, regardless of the dispersion method.

[0026] The present invention will now be described in more detail.

[0027] In the method according to the invention, Y or R 1 , R 2 , R 3 It may be advantageous to use two or more silanes, each of which may be identical or non-identical in pairs.

[0028] Advantageously, the at least one silane can be chosen from 3-glycidyloxypropyltriethoxysilane, abbreviated GLYEO, 3-aminopropyltriethoxysilane, abbreviated AMEO, glycidyloxypropyltrimethoxysilane, abbreviated GLYMO, 3-aminopropyltrimethoxysilane, abbreviated AMMO, or a mixture of these silanes.

[0029] More preferably, the at least one silane is bis(triethoxysilylpropyl)tetrasulfide, bis(triethoxysilylpropyl)disulfide, 3-thiocyanatopropyltriethoxysilane, γ-aminopropyltriethoxysilane, Dynasylan® SIVO 214, γ-aminopropyltrimethoxysilane, bis(triethoxysilylpropyl)amine, bis(trimethoxysilylpropyl)amine, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, triaminofunctional silanes, benzylaminosilane (50% in MeOH), benzylaminosilane (60% in water), vinylbenzylaminosilane (42% in MeOH), vinylbenzylaminosilane (40% in water), polyazamide silane (53% in MeOH), quaternary aminosilane (48% in water), methacrylamide silane (40% in water), γ-aminopropylsilanol (40% in water), γ-aminopropylsilanol (88% in water), vinylaminoalkylsilanol (60% in water), VPS 1208, triaminofunctional silanol (40% in water), 3-ureidopropyltrimethoxysilane, 3-ureidopropyltriethoxysilane (50% in methanol), 3-ureidopropyltriethoxysilane (with 10% EtOH), gamma-glycidoxypropyltrimethoxysilane, gamma-glycidoxypropyltriethoxysilane, gamma-methacryloxypropyltrimethoxysilane (MEMO), gamma-methacryloxypropyltriethoxysilane (MEEO), vinyltri ... The alkylsilane may be selected from trimethoxysilane (VTMO), vinyltriethoxysilane (VTEO), oligomeric alkylsilane (50% in water), polyether functional trimethoxysilane, vinyltrimethoxysilane (VTMO), 3-methacryloxypropyltriethoxysilane (MEEO), 3-methacryloxypropyltrimethoxysilane (MEMO), octyltrimethoxysilane (OCTMO), octyltriethoxysilane (OCTEO), or a combination of these silanes.

[0030] All of these advantageously usable silanes are available from Evonik Resource Efficiency GmbH, Rodenbacher Chaussee 4, 63457 Hanau, Germany.

[0031] Particularly preferably, the silane may be selected from 3-glycidyloxypropyltriethoxysilane (GLYEO), 3-aminopropyltriethoxysilane (AMEO), glycidyloxypropyltrimethoxysilane (GLYMO), 3-aminopropyltrimethoxysilane (AMMO), or a mixture of these silanes.

[0032] Very particularly preferably, glycidyloxypropyltriethoxysilane (GLYEO) can be used.

[0033] In the method according to the invention, the sum of the weight fractions of the at least one silane may range from 0.1 to 70% by weight, advantageously from 5 to 50% by weight and even better from 25 to 40% by weight, wherein the sum of the weight fraction of the silane and the weight fraction of the graphene material is 100% by weight.

[0034] When the weight fraction of silane used is 50 wt% in total, the weight ratio of graphene material to silane is 1:1.

[0035] The at least partial reaction in the method according to the invention can be carried out at a temperature in the range of 50-150° C., preferably in the range of 80-110° C. These temperatures can further be adjusted depending on the at least one silane, the graphene material and the mode of mixing.

[0036] For the mixing in the process according to the invention, it is possible to advantageously use a mixer granulator, a vessel equipped with grinding balls, a ball mill, a three-roll mill, a stirrer or a vessel equipped with a paddle.

[0037] The functionalization in the method according to the invention results in granules with higher bulk and tap densities than non-functionalized graphene material without compression. This is surprising, since in conventional methods, compression is generally required for the production of granules. However, in the method according to the invention, it can be advantageous to perform compression by mixing, for example by using a three-roll mill.

[0038] In the claimed method, with or without compaction, granules are obtained when at least one silane is used in a weight fraction of at least 5 wt.-%, particularly preferably at least 10 wt.-%, and further preferably at least one silane is used in a weight fraction of 0.1-70 wt.-%, advantageously 5-50 wt.-%, and further preferably 25-40 wt.-%, wherein the sum of the weight fraction of the silane and the weight fraction of the graphene material is 100 wt.-%.

[0039] Furthermore, it may be advantageous to prepare at least one silane prior to mixing, as is carried out in the examples according to the invention, which allows for a pre-functionalization of at least one silane.

[0040] Preferably, a defined amount of at least one silane can be added to an alcohol-water mixture, particularly preferably an ethanol-demineralized water mixture, very particularly preferably a mixture of 95% by volume of ethanol and 5% by volume of demineralized water, and the preparation thus obtained can be stirred for a period of time, preferably from 1 to 100 minutes, particularly preferably about 10 minutes, at room temperature.

[0041] Furthermore, it may be advantageous to adjust the demineralized water to a defined pH value using an acid, preferably HCl, advantageously to a pH value in the range from 4.5 to 5.5. A defined amount of at least one silane can then be added to this preparation and the preparation thus obtained can be stirred for a period of time, preferably from 1 to 100 minutes, particularly preferably about 10 minutes, at room temperature.

[0042] It may likewise be advantageous to add a defined amount of at least one silane to ethanol (pa) and to stir the preparation thus obtained for a period of time, preferably between 1 and 100 minutes, particularly preferably about 10 minutes, at room temperature.

[0043] In all of these options, it may then be advantageous to obtain a transparent phase.

[0044] The preferred preparation differs from conventional approaches in that only water or water-ethanol mixtures are used during pre-functionalization.

[0045] In the present invention, "room temperature" means a temperature of 20°C.

[0046] As already mentioned, the method according to the invention allows to obtain functionalized graphene materials with increased bulk and tap densities compared to conventional graphene materials. Moreover, as shown in the examples, the dust generated during its processing is significantly less. In particular, the functionalized graphene materials obtained according to the invention can be better integrated into various matrix systems. Moreover, the functionalized graphene materials obtained according to the invention can be more quickly and / or more easily fed into such systems.

[0047] Even more surprisingly, the flowability of the graphene material functionalized according to the invention compared to the non-functionalized graphene material surprisingly shows little change or is even better.

[0048] In the present invention, the flowability is determined by placing a specified amount in a drum and rotating the drum uniformly, as shown diagrammatically in FIG. 6. A camera is then used to check the angle at which the material starts to avalanche. In FIG. 6, the directions of rotation are shown by arrows. The smaller the so-called "avalanche angle" (ava,h) between the surface formed by the particles at the time of the avalanche and the horizontal (h), the higher, i.e., the better, the flowability of the material. The avalanche angle (ava) between the horizontal (h) is measured mathematically in a positive direction. Details of the measurement of flowability can be cited, for example, from the paper by Amado, "Advances in SLS powder characterization", 22nd Annual International Solid Freeform Fabrication Symposium - An Additive Manufacturing Conference, SFF, 2011, pp. 438-452.

[0049] In the method according to the invention, it may be advantageous to use at least one silane in a weight fraction of at least 30% by weight. Above such a weight fraction, the avalanche angle decreases as the proportion of the at least one silane increases. Advantageously, the weight fraction of the at least one silane that can be used ranges from 30 to 70% by weight, advantageously from 30 to 50% by weight and even better from 30 to 40% by weight, the sum of the weight fraction of the silane and the weight fraction of the graphene material being 100% by weight.

[0050] The functionalized graphene material obtained by the method according to the invention is therefore likewise a subject of the present invention.

[0051] Advantageously, the functionalized graphene material according to the invention or obtained according to the invention has a bulk density of 300-900 g / l, more advantageously 500-800 g / l, and / or a tapped density of 300-900 g / l, advantageously 500-800 g / l, and / or a dust reduction of 50-80%, advantageously 55-75%.

[0052] The bulk or tap density of the graphene materials functionalized and non-functionalized according to the invention is measured in accordance with DIN 53912 or DIN / ISO 787.

[0053] The dust generation is measured in the present invention in accordance with DIN 55992 using a Heubach Dustmeter Type I dust generator in the rotary mode.

[0054] In the examples, the results of the dust generation measurement were the weight of dust generated by the non-functionalized graphene material and the graphene material functionalized according to the present invention, respectively. In the present invention, the dust generation reduction rate is the difference between the weight of the dust measured according to DIN 55992 for a non-functionalized graphene material and the weight of the dust for a graphene material functionalized according to the invention; - the weight of the dust of non-functionalized graphene material and This is the ratio expressed as a percentage.

[0055] The mentioned further advantage of the functionalized graphene materials according to the invention or obtained according to the invention, that their flowability is unaltered or improved by the weight fraction of at least one silane, means that said materials can be used in at least the same application areas as non-functionalized materials, but are more easily processed and do not have the disadvantages mentioned for conventional graphene materials.

[0056] Thus, the use of the functionalized graphene material according to the invention or obtained according to the invention as filler, as corrosion inhibitor in coatings, for anti-icing, as active and / or electrode material in batteries, in composites and / or foams for modifying the mechanical, thermal, electrical and tribological properties as well as the flame retardancy, in tire rubbers, in transmission and / or engine oils, in metal processing, in membranes is likewise a subject.

[0057] In tire rubbers, the use according to the invention has the advantage of improving thermal and / or electrical properties as well as rolling resistance, wet grip performance and wear resistance. The claimed use in oils improves tribological properties such as friction, wear, heat dissipation, etc.

[0058] Advantageously, the functionalized graphene material according to the invention or obtained according to the invention comprises in standard thermoplastics, advantageously chosen from PE, PP, PS, PVC, - in technical thermoplastics, advantageously PET, PMMA, PC, POM, PA, in high-performance thermoplastics, preferably PPS, PEEK, PES, in copolymers, elastomers, advantageously silicones, and more preferably RTV, HTV, LSR, in polyurethanes, rubbers, preferably SBR, BR, natural rubber, in thermosetting resins, preferably polyurethanes, polyester resins, phenolic resins, epoxy resins, acrylate resins, silicone resins, in a solvent, preferably apolar aprotic, polar aprotic, protic solvent, in oils, preferably mineral oils, silicone oils, process oils It can be used. [Brief description of the drawings]

[0059] [Figure 1] FIG. 1 is a diagram showing a schematic operation mode of a three-roll mill. [Diagram 2] A diagram showing a Heubach dust meter type I dust generator. [Diagram 3] Diagram showing a tapping volumeter (ISO 787-11, October 1995 edition). [Figure 4] FIG. 1 shows the bulk and tap densities of graphene materials (unfunctionalized and functionalized). [Diagram 5]FIG. 2 shows the bulk density of the graphene material functionalized according to the present invention versus the amount of silane GLYEO used. [Figure 6] Diagram showing the functioning principle (schematic diagram) of the Revolution Powder Analyzer. [Figure 7] FIG. 1 shows the average angle of the surface of the functionalized material at the onset of avalanche versus the weight fraction of the silane GLYEO, averaged over 150 avalanche events. [Figure 8] Figure 1 shows images of the flowability measurements of functionalized graphene materials with different weight fractions (wt%) of silane GLYEO, measured with a Revolution Analyzer. [Figure 9] FIG. 13 shows the avalanche angles of functionalized graphene materials with different weight fractions of the silane GLYEO before and after the mixing program. [Figure 10] FIG. 1 shows the avalanche energy of graphene materials functionalized with silane GLYEO versus the weight fraction of silane GLYEO.

[0060] The present invention will now be described by way of example.

[0061] Example A. Functionalization of Graphene in a Flask Silane GLYEO was prepared before use as follows: 3 ppw amount of ethanol-demineralized water mixture (95% by volume ethanol, 5% by volume demineralized water) was adjusted to a pH value in the range of 4.5-5.5 using HCl. 1 ppw amount of silane was then carefully added to this with a syringe and stirred for about 10 minutes at room temperature. This resulted in a pre-functionalization of the silane. A transparent phase was obtained.

[0062] Graphene oxide was selected as the graphene material. 4 ppw of this graphene oxide was charged into a round-bottom flask equipped with a paddle, and 4 ppw of the prepared transparent phase was added. Partial reaction was carried out in a rotary evaporator at 100° C. under a pressure of 30 hPa for 3 hours.

[0063] The graphene material thus obtained, functionalized according to the invention, was then purified in a Soxhlet apparatus with ethanol (pa) to remove excess silane, pre-dried overnight under suction in a hood and then dried in a rotary evaporator at 100 °C and 30 hPa pressure for 3 h.

[0064] Example B: Functionalization of graphene in a laboratory mixer-granulator Silane GLYEO was prepared before use as follows: 3 ppw of demineralized water was adjusted to a pH value in the range of 4.5-5.5 using HCl. To this was carefully added 1 ppw of silane via syringe and stirred for about 10 minutes at room temperature. A clear phase was obtained.

[0065] Graphene oxide was selected as the graphene material. The graphene material was charged in an amount of 4 ppw and 4 ppw of the transparent phase was charged into a laboratory mixer granulator. The partial reaction was carried out in the mixer at 100° C. and 300 rpm for 3 hours.

[0066] The graphene material thus obtained, functionalized according to the invention, was then purified in a Soxhlet apparatus with ethanol (pa) to remove excess silane, pre-dried overnight under suction in a hood and then dried in a rotary evaporator at 100 °C and 30 hPa pressure for 3 h.

[0067] Example C. Functionalization of Graphene with Ball Mill Silane GLYEO was prepared prior to use as follows: 3 ppw amount of ethanol (pa) was charged. To this was carefully added 1 ppw amount of silane via syringe and stirred at room temperature for about 10 minutes. A clear phase was obtained.

[0068] Graphene oxide was selected as the graphene material. This graphene material was loaded into the grinding vessel of a ball mill in an amount of 4 ppw, and 4 ppw of a transparent phase was added. In addition, 4 ppw of grinding balls with diameters of 2 to 10 mm were added. The partial reaction was carried out in the ball mill at a rotation speed of 600 rpm for 15 minutes.

[0069] The graphene material thus obtained, functionalized according to the invention, was then purified in a Soxhlet apparatus with ethanol (pa) to remove excess silane, pre-dried overnight under suction in a hood and then dried in a rotary evaporator at 100 °C and 30 hPa pressure for 3 h.

[0070] Example D. Functionalization of Graphene on a Three-Roll Mill Silane GLYEO was prepared prior to use as follows: 3 ppw amount of ethanol (pa) was charged. To this was carefully added 1 ppw amount of silane via syringe and stirred at room temperature for about 10 minutes. A clear phase was obtained.

[0071] Graphene oxide was selected as the graphene material, and the graphene material was filled into a glass beaker in an amount of 4 ppw, and the transparent phase was applied in an amount of 4 ppw.

[0072] The reaction mixture was homogenized by stirring with a metal spatula. The mixture was then slowly and evenly spread onto the rolls of a three-roll mill. The rolls of this mill were made of SiC, and the temperature was controlled by an oil bath at 100°C oil temperature and 60°C roll surface temperature. An infrared thermometer was used for temperature control.

[0073] The rolls were operated at different speeds and directions of rotation: roll 1 was operated at 12 rpm, roll 2 at 36 rpm and roll 3 at 110 rpm, which is shown diagrammatically in FIG.

[0074] The rolls were spaced apart at a specified distance, ie, the distance between roll 1 and roll 2 was 15 μm, and the distance between roll 2 and roll 3 was 5 μm.

[0075] At this time, depending on the amount of material applied, the force is 1 to 6 N / mm 2 The material was discharged by a scraper arranged on roll 3.

[0076] The graphene material thus obtained, functionalized according to the invention, was then purified in a Soxhlet apparatus with ethanol (pa) to remove excess silane, pre-dried overnight under suction in a hood and then dried in a rotary evaporator at 100 °C and 30 hPa pressure for 3 h.

[0077] Example E: Measurement of the properties of functionalized graphene 1) Measurement of dust generation rate according to DIN 55992-1 (June 2006 edition) A Heubach Dustometer Type I dust generator was used, as shown diagrammatically in Figure 2. The construction details of this device are known to those skilled in the art.

[0078] Graphene oxide was chosen as the graphene material. In a rotational manner, the amount of dust generated was measured for non-functionalized graphene material or for graphene material functionalized according to the invention. A standard setup according to DIN 55992-1 was chosen: - 30 rpm - Air flow rate 20L / min - 100L - 5 minutes

[0079] First, measurements of the amount of dust generated were performed using various amounts of graphene oxide, a non-functionalized graphene material. The more the amount of graphene material, i.e., the larger the initial weight, the more the amount of dust released, which had a positive effect on the experimental error. However, it was confirmed that if the initial weight was too large, the air passages in the device could be blocked, leading to an underestimation of the amount of dust released. Such results were rejected. The measurement results are shown in Table 1.

[0080] [Table 1]

[0081] Non-functionalized graphene released 3.4% dust from an initial weight of 5 g and 3.0% dust from an initial weight of 7.5 g. The dust was captured on a filter and weighed. For both measurements, 100 L of air was drawn into the dust meter for a specified time.

[0082] Next, for the graphene material functionalized according to the present invention from Example C, the amount of dust generated was measured with the initial weight of the functionalized graphene material set to 5 g or 7.5 g. The results are shown in Table 2.

[0083] [Table 2]

[0084] The weight of dust measured in the filter in these experiments was clearly less than in the case of non-functionalized graphene material. Measurements with 5 g of graphene material functionalized according to the invention resulted in 1.0% dust release. Compared to the non-functionalized graphene material, this corresponds to a reduction of 68%. A similar reduction in dust release of 68% was achieved with an initial weight of 7.5 g.

[0085] 2) Measurement of bulk density and tap density The bulk and tap densities of the graphene material functionalized according to the invention and of the non-functionalized graphene material, respectively, were measured using a tapping volumeter in accordance with DIN 53912 and DIN / ISO 787. The tapping volumeter is shown diagrammatically in FIG.

[0086] The graphene material functionalized according to the present invention had agglomerates with diameters of 0.5 mm or less that were not removed because this would have resulted in a weight loss that would have made a representative analysis of the bulk material impossible.

[0087] For the bulk density measurements, each material was slowly added to a tared 100 ml graduated cylinder through a funnel. After the filling process was completed, a 1 minute wait was given to allow the air to escape and the fill volume after the air evacuation was kept constant. At this time, the graduated cylinder had to be left to stand and, if necessary, the fill level was at most levelled with a spatula.

[0088] After reading the filling level, the filled weight was measured. The bulk density was calculated by weight per filled volume. The density was measured in two batches for each material. For the tapped density measurement, the graduated cylinder was mechanically tapped 1250 times according to DIN / ISO 787.

[0089] The results are shown in Figure 4. For the graphene material functionalized with GLYEO according to the invention, the bulk density is greater than 600 g / l, which is more than three times higher than the 177 g / l of the non-functionalized graphene material. Also, the tapped density of this functionalized graphene material is greater than 700 g / l, which is more than three times higher than the 230 g / l of the virgin graphene. Thus, a denser graphene material was obtained by the method according to the invention. Figure 4 further shows the ratio of bulk density to tapped density in "compressibility" (%).

[0090] FIG. 5 illustrates the effectiveness of the method according to the invention based on the relationship between the bulk density of the graphene material functionalized according to the invention and the amount of silane GLYEO used.

[0091] Here, the weight fraction of the silane GLYEO was varied from 10 to 50 wt%. It was found that with 10 wt% GLYEO the bulk density started at 502 g / l, which increased to a value of about 650 g / l with the use of 50 wt% GLYEO. From Figure 5, a linear relationship can be seen between the GLYEO fraction and the bulk density.

[0092] 3) Measurement of liquidity The influence of the functionalization of the graphene material according to the invention on its flowability was studied using a Revolution Powder Analyzer, Model Rev2015 from PS Prozesstechnik GmbH. Here, a defined amount was placed in a rotating drum, as shown in FIG. 6, and a camera was used to study the angle at which the material started to avalanche. The smaller the avalanche angle (ava,h) between the surface formed by the particle at the time of the avalanche and the horizontal (h), the better the flowability of the material was indicated. The avalanche angle was measured in the mathematically positive direction from (ava) to the horizontal (h). The operating mode of the Powder Analyzer and the measurement variables determined thereby are known to the person skilled in the art. Details of the measurement of the flowability can be taken for example from the paper by Amado, “Advances in SLS powder characterization”, 22nd Annual International Solid Freeform Fabrication Symposium - An Additive Manufacturing Conference, SFF, 2011, pp. 438-452.

[0093] Following the manufacturer's instructions, 100 ml of material was poured into a 100 mm diameter PET drum. The fill volume was measured by stirring to remove air pockets as specified, but without tapping.

[0094] The measurement parameters of the flowability program corresponded to the standard settings for dark powders: 0.5rpm 150 avalanches Avalanche Threshold 0.65% Camera: Shutter speed 6ms, Gain 6dB (black powder), 10 frames / sec

[0095] Figure 7 shows the average angle of each powder surface obtained from 150 avalanches for graphene material produced according to the invention with each fraction of silane GLYEO. The higher the angle at the start of the avalanche, the worse the flowability of the material. The flowability was found to be constant for silane loadings between 0 and 30 wt%.

[0096] Above 30 wt. % of silane GLYEO, the avalanche angle decreased with increasing silane fraction from about 60° to less than 50° at 50 wt. % of silane GLYEO. Thus, it was found that the addition of more than 30 wt. % of silane GLYEO resulted in a clear improvement in flowability.

[0097] FIG. 8 shows camera images taken with a Revolution Powder Analyzer at the moment of avalanche initiation of the functionalized graphene material according to the present invention, each with different weight fractions of the silane GLYEO.

[0098] To investigate the stability of graphene materials produced according to the present invention after extended handling, a 5.8 hour Revolution Analyzer mixing program was used, which consisted of 150 cycles of alternating relatively fast mixing periods of 20 seconds at 5 rpm with slower mixing periods of 120 seconds at 1 rpm.

[0099] After the program was completed, the flowability was measured again as described above. As shown in Figure 9, the average avalanche angle of the non-functionalized graphene material clearly increased from 59° to 64°, indicating a worsening of the flowability. In contrast, the avalanche angle of the graphene material functionalized with the silane GLYEO according to the present invention showed no or little increase after prolonged mixing.

[0100] Another indicator of the flowability of the graphene material is the avalanche energy, which was also measured. The change in avalanche energy with respect to the weight fraction of silane was very small, and the lower the energy for avalanche initiation, the better the flowability of the material.

[0101] In FIG. 10, it can be seen that the optimum is at about 30-35% by weight of the silane GLYEO.

Claims

1. 1. A method for functionalizing a graphene material, comprising the steps of: at least partially reacting the graphene material with at least one silane; The at least one silane has the structure Y-Si(OR 1 ) (OR 2 ) (OR 3 ) Y is a branched or unbranched alkyl, olefinic or aromatic group, a combination of said groups, or an organofunctional group; Carboxy group, carbonyl group, hydroperoxycarbonyl group, halogenyl group, sulfo group, sulfino group, sulfeno group, cyano group, formyl group, oxo group, thioxo group, hydroxy group, amino group, imino group, hydrazino group, epoxy group, sulfanyl group, fluoro group, and combinations of the above groups. or a combination of alkyl, olefinic or aromatic groups with said organic functional groups; R 1 , R 2 , R 3 are branched or unbranched, identical or non-identical pairs of alkyl, olefinic or aromatic groups, wherein the at least partial reacting occurs during mixing of the silane and the graphene material.

2. Y or R 1 , R 2 , R 3 The method of claim 1 , wherein two or more silanes are used that are identical or non-identical in pairs.

3. 2. The method of claim 1, wherein the at least one silane is selected from 3-glycidyloxypropyltriethoxysilane [GLYEO], 3-aminopropyltriethoxysilane [AMEO], glycidyloxypropyltrimethoxysilane [GLYMO], 3-aminopropyltrimethoxysilane [AMMO], or a mixture of said silanes.

4. the sum of the weight fractions of said at least one silane is in the range of 0.1 to 70% by weight, advantageously in the range of 5 to 50% by weight and even better in the range of 25 to 40% by weight, 4. The method of claim 1, wherein the sum of the weight fraction of the silane and the weight fraction of the graphene material is 100% by weight.

5. A process according to any one of claims 1 to 4, wherein the at least partial reaction is carried out at a temperature in the range of from 50 to 150°C, preferably in the range of from 80 to 110°C.

6. 6. The method according to claim 1, wherein the mixing is carried out using a mixer granulator, a vessel equipped with grinding balls, a ball mill, a three-roll mill, a stirrer, or a vessel equipped with a paddle.

7. A functionalized graphene material obtained by the method according to any one of claims 1 to 6.

8. a bulk density of from 300 to 900 g / l, preferably from 500 to 800 g / l, and / or a tap density of from 300 to 900 g / l, preferably from 500 to 800 g / l, and / or A reduction in dust generation of 50 to 80%, preferably 55 to 75%.

8. The functionalized graphene material of claim 7, characterized in that

9. 9. Use of the functionalized graphene material according to claim 7 or 8 as a filler, as a corrosion inhibitor in coatings, for anti-icing, as active and / or electrode material in batteries, in composites and / or foams for modifying the mechanical, thermal, electrical and tribological properties and flame retardancy, in tire rubber, in transmission and / or engine oils, in metal processing, in membranes.

10. In standard thermoplastics, preferably thermoplastics selected from PE, PP, PS, PVC, in technical thermoplastics, preferably PET, PMMA, PC, POM, PA, In high performance thermoplastics, preferably PPS, PEEK, PES, Copolymers, elastomers, advantageously silicones, more preferably RTV, HTV, LSR, Polyurethane, rubber, preferably SBR, BR, natural rubber, in thermosetting resins, preferably polyurethanes, polyester resins, phenolic resins, epoxy resins, acrylate resins, silicone resins, In a solvent, preferably apolar aprotic, polar aprotic, protic solvent, In oils, preferably mineral oils, silicone oils, process oils, 10. The use according to claim 9.